Ответы и объяснения

Лучший Ответ!
2014-01-16T22:26:16+00:00
Используя формулу двойного угла:
\sin\left ( 2\alpha  \right )=2\sin \alpha \cdot \cos \alpha
получим
\sin\left(3 x\right )\cdot\cos\left ( 3 x\right )=\frac{1}{2}\sin\left ( 2\cdot 3x\right ) = -\frac{1}{2}
\sin\left ( 6x\right ) = -1
 6x = -\frac{\pi}{2} + 2\pi k, где  k\in\mathbb{Z}
 x = -\frac{\pi}{12} + \frac{\pi k}{3}, где  k\in\mathbb{Z}
2014-01-16T22:28:32+00:00
sin3x • cos3x= -1/2   
 sin3x * cos3x+1/2=0
(2cos3x * sin3x+1) : 2 * (2cos3x * sin3x+1)/2=0    x =-π/12+(πа)/3
     а - целое число